Integration of Ethnic Tengger Local Cultural Values in Merdeka Curriculum for Elementary Education Level A-C - Amiruddin, Mochammad; Munif, Munif; Sholikhudin, M. Anang (ISLAMIKA, 2025)
This study examines the integration of local cultural values of the Tengger ethnic community into the Merdeka Curriculum at the elementary education level, specifically across phases A to C. Utilizing a qualitative case study design, data were collected through in-depth interviews with educators and school administrators, direct classroom observations, and analysis of curricular and instructional documentation in public elementary schools located in Tosari District, Pasuruan Regency. The findings reveal that core Tengger cultural values, such as deliberative consensus, communal cooperation (gotong royong), and interreligious harmony are systematically embedded within thematic learning activities and Pancasila Student Profile (P5) projects. These values are internalized through pedagogical strategies that align with Lickona’s framework of moral knowing, moral feeling, and moral action, fostering holistic character development among students. Teachers contextualize learning content by linking curriculum competencies to students’ lived cultural experiences, thereby enhancing relevance, engagement, and ethical understanding. The study demonstrates that the Merdeka Curriculum provides a flexible platform for the incorporation of local wisdom, enabling culturally responsive and sustainable character education. These findings highlight the potential of curriculum localization to strengthen national education goals while preserving indigenous identity and community values within formal schooling.